Creditor´s liability in the Regulation 655/2014, on the European Account Preservation Order - Villamarín López, María Luisa (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
Regulation 655/2014, which establishes the European Account Preservation Order, has provided a series of mechanisms to balance the privileged position in which it places cross-border creditors when they request such measure inaudita parte debitoris. In this article, we address critically the two fundamental instruments that are envisaged for this purpose: first, the provision of security, which, as a general rule, is configured as one of the most important requirements of these measures (Art. 12); second, the liability regime due to the creditor for the damages derived from the adoption of the European order (Art. 13), which has been foreseen as a minimum standard and, therefore, has left almost all aspects of this responsibility for the application of national laws.